Integration of AI into the CREATE Model to Foster Student Creativity in Molecular Geometry Learning Using TCOF Assessment and Williams’ Indicators - Erika Ayu Andini; Wawan Wahyu; Ali Kusrijadi (Universitas Cokroaminoto Palopo, 2026)
The urgency of this study is to enhance students' creativity in molecular geometry learning by integrating AI into the CREATE model with TCOF assessment and Williams' creativity indicators. This study aims to analyze the implementation of the CREATE (Connecting, Restructuring, Elaborating, Applying, Tasking, Evaluating) learning model assisted by Artificial Intelligence (AI), as well as students’ creativity levels at each stage of molecular geometry learning through the creation of molecular models using materials from the surrounding environment. This study employed a qualitative descriptive method with a sample of 20 twelfth-grade students divided into 5 groups. The implementation of the learning process was measured using the TCOF and LTT scales based on Williams’ indicators, which include fluency, flexibility, elaboration, originality, and evaluation. The TCOF assessment results were categorized as “Very Adequate” across all stages: the “In-Class Activities that Encourage Creativity” and “Overall Learning Methods to Foster Creativity” categories scored 100%; the “Educator’s Response to Students’ Ideas” scored 97.66%; and the “Strate gy in Asking Questions” scored 95.33%. The achievement of creativity through LTT demonstrates a design capable of developing creativity in a structured, step-by-step manner. In individual assessments, evaluation reached 100% in all three stages (Connecting, Restructuring, Tasking). The Elaborating stage achieved the highest individual scores on the indicators of fluency (88.75%), flexibility (87.50%), elaboration (91.25%), and evaluation (95%), all falling into the “highly creative” category. In the group assessment, the Flexibility indicator (100%) was achieved in all four stages; Originality was 90% in the Applying and Tasking stages; while fluency in the Evaluating stage (80%) was categorized as “creative.” The results of this study indicate that the integration of the CREATE model with the assistance of AI technology can foster students’ creativity in a gradual and structured manner.